Bonded ceramic body and method for manufacturing same
By joining multiple ceramic parts with plasma-resistant glass or glass-ceramic bonding materials to form a plasma-resistant ceramic body, the problem of ceramic components in the plasma etching chamber is solved, and a longer service life is achieved. Lower pollution.
Patent Information
- Application Number
- CN202411613876.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-26
- Filing Date
- 2021-05-25
- Publication Date
- 2025-02-14
AI Technical Summary
The ceramic components used in the plasma etching chambers are susceptible to erosion and corrosion by the plasma environment, resulting in short life, frequent tool shutdowns and contamination problems.
Using a plasma-resistant ceramic body formed of a plurality of pieces, a plurality of ceramic parts are bonded together by using a plasma-resistant glass or glass-ceramic bonding material to form a bonded ceramic body with high purity and low impurity content.
It achieves improving the corrosion resistance and corrosion resistance of ceramic components in a plasma environment, extending the service life of components, reducing pollution and tool downtime.
Smart Images

Figure CN119430982A_ABST
Abstract
Description
[0001] This application is a divisional application of the Chinese invention patent application with application number 202180036993.6, application date May 25, 2021, and invention name “Plasma-resistant ceramic body formed by multiple parts”. Technical Field
[0002] Embodiments of the present disclosure relate to a plasma resistant ceramic body formed from a plurality of pieces or parts for use as a component in a plasma etching chamber or a deposition chamber. The ceramic parts are joined or bonded using a plasma resistant glass or glass ceramic bonding material to form a joined ceramic body. In addition, embodiments of the present disclosure also provide a method for making the joined ceramic body and making a plasma resistant ceramic component from the body. Background Art
[0003] This section discloses subject matter related to the disclosed embodiments.The background art discussed in this section is not intended to legally constitute prior art, either explicitly or implicitly.
[0004] Glass is an amorphous solid and therefore has no crystalline structure. Glass ceramics are made by first forming the glass and then at least partially crystallizing the glass by carefully controlling the heat treatment and cooling rate. This produces a glass ceramic material with a microstructure having crystalline regions surrounded by a glass amorphous matrix. The glass matrix fills the voids and pores that may otherwise be present in the ceramic material. The properties of the glass ceramic material can be adjusted according to the composition and processing to achieve unique properties that are different from glass or ceramic materials.
[0005] During the processing of semiconductor substrates, plasma is usually used to remove materials on chamber walls and substrates. Plasma conditions produce a highly corrosive and highly aggressive environment and expose the walls and components of the chamber to significant ion bombardment and chemical corrosion. The ion bombardment combined with plasma chemicals and / or etching byproducts can produce significant surface roughening, erosion, corrosion, and corrosion-erosion of the surfaces of the processing chamber exposed to the plasma. Therefore, surface materials are removed by physical and / or chemical attacks. The attacks lead to problems including short part life, which leads to extended tool downtime, increased consumables costs, particulate contamination, transition metal contamination on the wafer, and process drift.
[0006] Due to the aggressive and corrosive nature of the plasma environment in such reactors, it is desirable to minimize particle and / or metal contamination. Therefore, it is desirable that the components and bonding materials (including consumables and other parts) designed for the manufacture of such equipment have suitably high erosion and corrosion resistance. In view of this, those plasma chamber components and bonding or joining materials having very high purity can provide a uniformly corrosion-resistant surface with few impurities, which can prevent corrosion and erosion during use. Such plasma chamber component parts have been formed of exemplary etch-resistant materials such as, but not limited to, aluminum oxide, yttrium oxide, one or more forms of yttrium aluminum oxide, and aluminum nitride, which provide corrosion and erosion resistance in a plasma environment. These exemplary etch-resistant bodies are disclosed in U.S. Provisional Patent Application No. 62 / 829,720, entitled “Controlled Porosity Yttrium Oxide for Etch Applications,” and U.S. Provisional Patent Application No. 62 / 936821, entitled “Ceramic Sintered Body for Corrosion Resistant Components,” both of which are incorporated herein by reference in their entirety.
[0007] Typical glasses used in various electronic device applications do not perform well in halogen-based plasma applications and / or high levels of alkali and alkaline earth elements and borosilicate compounds, thereby preventing their use in applications requiring high purity. Additionally, the presence of boron in many glass compositions may be incompatible with semiconductor device manufacturing processes.
[0008] Plasma processing chambers have been designed to include components such as disks, showerheads or windows, nozzles, chamber liners, various rings (such as focus rings and guard rings), and cylinders that confine the plasma above the wafer being processed.
[0009] In order to meet the continuous pursuit of finer features and node sizes, chamber components used in processing semiconductor substrates are required to have greater functionality, thereby necessitating more complex structures. These structures may have multiple layers, embedded elements, parts or patterned layers of different materials combined into a single body or component. In order to manufacture these higher complexity structures, it may be required to combine or bond multiple etch-resistant components to form components such as wafer support components (e.g., suction cups or electrostatic chucks (ESC)), RF or dielectric windows, syringes or nozzles with multiple openings for different process gases, process rings or other rings with embedded wires, meshes or other elements to provide electrical functionality, and other components. The use of arrays of materials combined in various configurations brings problems due to different material properties. For example, the mechanical properties of the bonding material (such as the coefficient of thermal expansion (CTE)) must be compatible with the mechanical properties of the ceramic components selected for use to avoid cracking and / or delamination due to thermal deviations generated during use in semiconductor manufacturing. In addition, the bonding process generally requires a pressure of about 0.15MPa and greater, such as up to 1.4MPa, to ensure sufficient bonding between the pieces. In addition, the bonding or bonding materials applied between ceramic components are continuously attacked by plasma in the same manner as the ceramic components and thus erode, corrode or accumulate contaminants and polymers, and are therefore subject to the same etching resistance requirements as the ceramic components themselves. Therefore, the corrosion and erosion resistance of chamber components in halogen plasma applications and the service life of these components may be limited by the bonding materials selected for use. There are continuous efforts to improve the plasma resistance of chamber components used in etching and deposition semiconductor processes, especially those components made of multiple pieces, to meet the more stringent design requirements required for prior art semiconductor processing chambers. The use of the materials and methods disclosed herein will provide performance improvements over the known technology.
[0010] Therefore, there is a need for a multi-piece corrosion- and erosion-resistant ceramic body joined by a corrosion- and erosion-resistant glass or glass-ceramic material. Summary of the invention
[0011] Starting from the foregoing related art, these and other needs are addressed by various embodiments, aspects and configurations as disclosed herein:
[0012] / 1 / A joined ceramic body, comprising: a first ceramic part, the first ceramic part comprising a first ceramic; a second ceramic part, the second ceramic part comprising a second ceramic; a joining layer, the joining layer being formed between the first ceramic part and the second ceramic part, wherein the joining layer has a bonding thickness between 0.5 μm and 20 μm and contains silicon dioxide having a total impurity content of 20 ppm and less relative to the mass of the joining layer.
[0013] / 2 / The joined ceramic body according to Embodiment 1, wherein the joining layer contains an amorphous glass phase having a total impurity content of 10 ppm and less relative to the mass of the joining layer.
[0014] / 3 / The joined ceramic body according to any one of the aforementioned embodiments 1 or 2, wherein the joining layer comprises a glass ceramic comprising an amorphous glass phase and at least one crystalline ceramic phase.
[0015] / 4 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 3, wherein the joining layer comprises at least one crystalline ceramic phase having a crystallinity in an amount of 5 volume % to 99 volume % of the joining layer.
[0016] / 5 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 4, wherein the joining layer comprises at least one crystalline ceramic phase having a crystallinity in an amount of 5 volume % to 90 volume % of the joining layer.
[0017] / 6 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 5, wherein the joining layer comprises at least one crystalline ceramic phase having a crystallinity in an amount of 5 volume % to 70 volume % of the joining layer.
[0018] / 7 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 6, wherein the joining layer comprises at least one crystalline ceramic phase having a crystallinity in an amount of 10 volume % to 60 volume % of the joining layer.
[0019] / 8 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 7, wherein the joining layer comprises at least one crystalline ceramic phase having a crystallinity in an amount of 10 volume % to 50 volume % of the joining layer.
[0020] / 9 / A joined ceramic body according to any one of the aforementioned embodiments 1 to 8, wherein the at least one crystalline ceramic phase comprises at least one selected from the group consisting of: mullite, alumina, Y2Si2O7, Y2SiO5 and Y3Al5O12 (yttrium aluminum garnet).
[0021] / 10 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 9, wherein the Y3Al5O12 (yttrium aluminum garnet) is polycrystalline.
[0022] / 11 / The joined ceramic body according to any one of aforementioned embodiments 1 to 10, wherein the joining layer has a total impurity content of 10 ppm and less relative to the mass of the joining layer.
[0023] / 12 / The joined ceramic body according to any one of aforementioned embodiments 1 to 11, wherein the joining layer has a total impurity content of 5 ppm and less relative to the mass of the joining layer.
[0024] / 13 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 12, wherein the joining layer has a total purity of 99.99% and higher relative to a purity of 100%.
[0025] / 14 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 13, wherein the joining layer has a total purity of 99.995% and higher relative to a purity of 100%.
[0026] / 15 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 14, wherein the joining layer has a total purity of 99.999% and higher relative to a purity of 100%.
[0027] / 16 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 15, wherein the joining layer has a total alkali or alkaline earth element content of 5 ppm and less relative to the mass of the joining layer.
[0028] / 17 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 16, wherein the joining layer has a bonding thickness of 1 μm to 15 μm.
[0029] / 18 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 17, wherein the joining layer has a bonding thickness of 3 μm to 10 μm.
[0030] / 19 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 18, wherein the joining layer has a bonding thickness of 4 μm to 8 μm.
[0031] / 20 / A joined ceramic body according to any one of the aforementioned embodiments 1 to 19, wherein the joining layer further comprises a rare earth oxide having a purity of 99.99% and higher relative to 100% purity of the joining layer and selected from the group consisting of: Y2O3, La2O3, CeO2, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Lu2O3 and combinations thereof.
[0032] / 21 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 20, wherein the joining layer further comprises an element selected from the group consisting of: Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu and combinations thereof.
[0033] / 22 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 21, wherein the first ceramic portion and the second ceramic portion include the same ceramic.
[0034] / 23 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 22, wherein the first ceramic and the second ceramic comprise different ceramics.
[0035] / 24 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 23, wherein each of the first ceramic part and the second ceramic part is selected from the group consisting of aluminum oxide, yttrium oxide, aluminum nitride, yttrium aluminum garnet (YAG; Y3Al5O 12 ), silicon carbide, quartz, mullite, SiAlON materials and combinations thereof.
[0036] / 25 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 24, wherein the first ceramic portion and the second ceramic portion are alumina.
[0037] / 26 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 25, wherein the joining layer has a coefficient of thermal expansion (CTE) of 0% to 10% of each of the first ceramic portion and the second ceramic portion.
[0038] / 27 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 26, wherein the joining layer has a coefficient of thermal expansion (CTE) of 0% to 5% of each of the first ceramic portion and the second ceramic portion.
[0039] / 28 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 27, wherein the first ceramic portion and the second ceramic portion have a total purity of 99.99% and higher relative to a purity of 100%.
[0040] / 29 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 28, wherein the first ceramic portion and the second ceramic portion have a total purity of 99.995% and higher relative to a purity of 100%.
[0041] / 30 / The joined ceramic body according to any one of the aforementioned embodiments 1 to 29, having a purity of 99.99% and higher relative to a purity of 100%.
[0042] / 31 / A method of manufacturing a bonded ceramic body, the method comprising: placing a powder of silicon dioxide between a surface of a first ceramic portion and a surface of a second ceramic portion to form a ceramic body assembly; increasing the temperature of the ceramic body assembly to a sintering temperature sufficient to bond the first ceramic portion and the second ceramic portion to form the bonded ceramic body; and lowering the temperature of the bonded ceramic body, wherein the silicon dioxide has a 25 m 2 / g to 50m 2 / g of specific surface area and a purity of 99.999% and higher relative to 100% purity, the method being characterized in that the method is carried out under conditions for preparing a joined ceramic body having the characteristics as disclosed in any one of the preceding embodiments.
[0043] / 32 / The method according to embodiment 31, wherein step a. further comprises a powder of aluminum oxide, wherein the aluminum oxide has a purity of 99.99% and higher.
[0044] / 33 / The method according to any one of embodiments 31 or 32, wherein step a. also includes a powder of at least one rare earth oxide having a purity of 99.99% and higher selected from the group consisting of: Y2O3, La2O3, CeO2, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Lu2O3 and combinations thereof.
[0045] / 34 / The method according to any one of embodiments 31 to 33, wherein the sintering temperature of step b. is between 1100°C and 1500°C.
[0046] / 35 / The method according to any one of embodiments 31 to 34, wherein step a. further comprises a powder of yttrium oxide having a purity of 99.995% and higher relative to 100% purity.
[0047] / 36 / According to any one of the methods described in embodiments 31 to 35, the method further includes the following steps: machining the bonded ceramic body to produce a bonded ceramic body component for use in a semiconductor processing chamber.
[0048] / 37 / A method according to any one of embodiments 31 to 36, wherein the bonded ceramic body component is selected from the group consisting of: a dielectric window or an RF window, a ring, a nozzle or a gas injector, a showerhead, a gas distribution plate, an etching chamber liner, a plasma source adapter, a gas inlet adapter, a diffuser, an electronic wafer chuck, a chuck, a positioning plate, an ion suppressor element, a panel and / or a protective ring in an etching chamber.
[0049] / 38 / A joined ceramic body for producing a semiconductor chamber component manufactured by the method according to any one of Embodiments 31 to 37.
[0050] / 39 / According to any one of embodiments 31 to 38, the joined ceramic body has a size of 100mm to 622mm, preferably 200mm to 622mm, preferably 300mm to 622mm, preferably 400mm to 622mm, more preferably 450mm to 622mm, more preferably 500mm to 622mm, more preferably 550mm to 622mm, with respect to the longest extension of the ceramic body.
[0051] / 40 / A plasma resistant composition comprising: silicon dioxide having a particle size between 30 nm and 200 nm and a specific surface area between 25 m2 / g and 50 m2 / g measured by the BET method; aluminum oxide; and at least one rare earth oxide selected from the group consisting of Y2O3, La2O3, CeO2, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Lu2O3 and combinations thereof; and a suspension medium, wherein the plasma resistant composition comprises a paste.
[0052] / 41 / The plasma resistant composition according to embodiment 40, wherein the silicon dioxide has an overall purity of at least 99.999% and higher relative to 100% purity.
[0053] / 42 / The plasma resistant composition according to any one of embodiments 40 or 41, wherein the at least one rare earth oxide comprises yttrium oxide having a purity of 99.99% and higher relative to 100% purity.
[0054] / 43 / The plasma resistant composition according to any one of embodiments 40 to 42, having an overall purity of at least 99.995% and higher relative to 100% purity.
[0055] / 44 / The plasma resistant composition according to any one of embodiments 40 to 43, wherein the suspension medium comprises a liquid selected from the group consisting of: water, ethanol, isopropanol, glycerol, and combinations thereof.
[0056] / 45 / The plasma resistant composition according to any one of embodiments 40 to 44, having a maximum particle size (d100) between 4 microns and 6 microns.
[0057] / 46 / The plasma resistant composition according to any one of embodiments 40 to 45, wherein the aluminum oxide has a purity of 99.99% and higher relative to 100% purity.
[0058] / 47 / The plasma resistant composition according to any one of embodiments 40 to 46, wherein the at least one rare earth oxide selected from the group consisting of Y2O3, La2O3, CeO2, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Lu2O3 and combinations thereof has a purity of 99.99% and higher.
[0059] / 48 / The plasma resistant composition according to any one of embodiments 40 to 47, wherein silicon dioxide is present in an amount of 25 wt.% to 60 wt.%, and the balance comprises a mixture of aluminum oxide in an amount of 25 wt.% to 50 wt.% and at least one rare earth oxide in an amount of 50 wt.% to 75 wt.%.
[0060] / 49 / The plasma resistant composition according to embodiment 48, wherein the rare earth oxide comprises yttrium oxide.
[0061] / 50 / The plasma resistant composition according to embodiment 49, which is used according to the method of any one of embodiments 31 to 39.
[0062] / 51 / A joined ceramic body, comprising: a first ceramic part and a second ceramic part of aluminum oxide; a joining layer, which is formed between the first ceramic part and the second ceramic part and has a bonding thickness of 0.5 μm to 20 μm, wherein the first ceramic part and the second ceramic part have a purity of 99.99% and higher, and the joining layer contains glass ceramics, which contain an amorphous glass phase and at least one crystalline ceramic phase, wherein the joining layer has a total impurity content of 20 ppm and lower relative to the mass of the joining layer.
[0063] / 52 / A bonding ceramic body, which comprises: a first ceramic part and a second ceramic part of yttrium aluminum garnet (YAG, Y3Al5O12); and a bonding layer, which is formed between the first ceramic part and the second ceramic part, wherein the first ceramic part and the second ceramic part have a purity of 99.99% and higher, wherein the bonding layer comprises glass ceramic, which comprises an amorphous glass phase and at least one crystalline ceramic phase selected from the group consisting of: yttrium aluminum garnet (YAG; Y3Al5O12), yttrium aluminum monoclinic (YAM, Y4Al2O9) and yttrium aluminum perovskite (YAP, YAlO3), wherein the bonding layer has a total impurity content of 20 ppm and lower relative to the mass of the bonding layer and a bonding thickness of 0.5μm to 20μm.
[0064] / 53 / A joined ceramic body, comprising: a first ceramic part and a second ceramic part of aluminum oxide; and a joining layer formed between the first ceramic part and the second ceramic part, wherein the first ceramic part and the second ceramic part have a purity of 99.99% and higher, and the joining layer comprises glass ceramic, which comprises an amorphous glass phase and at least one crystalline ceramic phase, wherein the at least one crystalline ceramic phase is selected from the group consisting of: mullite, aluminum oxide, Y2Si2O7, Y2SiO5 and Y3Al5O12 (yttrium aluminum garnet), wherein the joining layer has a total impurity content of 20 ppm and lower and a bonding thickness between 0.5 μm and 20 μm.
[0065] / 54 / A bonding ceramic body, which includes: a first ceramic part and a second ceramic part of yttrium aluminum garnet (YAG, Y3Al5O12); a bonding layer, which is formed between the first ceramic part and the second ceramic part, and the first ceramic part and the second ceramic part have a purity of 99.99% and higher, and the bonding layer contains glass ceramics, which contain an amorphous glass phase and at least one crystalline ceramic phase selected from the group consisting of: mullite, alumina, Y2Si2O7, Y2SiO5 and Y3Al5O12 (yttrium aluminum garnet), and the bonding layer has a total impurity content of 20 ppm and lower relative to the mass of the bonding layer, and the bonding layer has a bonding thickness of 0.5μm to 20μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 Embodiments of joined ceramic bodies according to the present disclosure are depicted.
[0067] Figure 2 Embodiments of joined ceramic bodies not in accordance with the present disclosure are depicted.
[0068] Figure 3 Shown are differential scanning calorimetry (DSC) results for glass-ceramic bonding materials as disclosed herein.
[0069] Figure 4 A semiconductor processing system according to an embodiment of the present technology is shown.
[0070] Figure 5 A wafer support assembly of chamber components having a chuck or electronic wafer chuck or electrostatic chuck (ESC) and a cover ring is shown.
[0071] Fig. 6A and Figure 6B Shown are plan views and detailed cross-sectional views of various rings for use in a semiconductor processing system as disclosed herein.
[0072] Figure 7 Shows the application Figure 4 , Figure 5 and representative cross-sectional views of the embodiment depicted in FIG. 6 , as well as other multi-piece ceramic bodies or components as disclosed herein.
[0073] Figure 8 is a ternary yttria-silica-alumina phase diagram showing the crystalline phases formed and the ratios and temperatures required to form them. DETAILED DESCRIPTION
[0074] Reference will now be made in detail to specific embodiments. Examples of specific embodiments are shown in the accompanying drawings. Although the present disclosure will be described in conjunction with these specific embodiments, it should be understood that this is not intended to limit the present disclosure to these specific embodiments. On the contrary, it is intended to cover alternatives, modifications and equivalents that may be included in the essence and scope defined by the appended claims. In the following description, many specific details are set forth to provide a thorough understanding of the disclosed embodiments. The present disclosure may be practiced without some or all of these specific details.
[0075] When the word "about" is used herein, the nominal value disclosed has an associated variation of + / - 10%.
[0076] Disclosed herein are materials and methods that can be used to fabricate chamber components for semiconductor and / or microelectromechanical (MEM) processing systems. Specifically, the materials and methods relate to bonding materials that can be used to bond separate structures together to fabricate ceramic body components that provide enhanced resistance to halogen-based process gases, and more specifically to fluorine-containing process gases such as used in etching and / or deposition semiconductor processes.
[0077] By way of example, and not limitation, these components made from the bonded structures may be chamber liners, RF or microwave windows, showerheads and / or gas distribution assemblies, focusing, shielding or clamping rings (as well as other ring designs known to those skilled in the art), gas injectors or nozzles, wafer chucks and / or electronic wafer chucks. The bonding materials, methods of making the bonding materials, and use in making plasma resistant ceramic body components as disclosed will enable the manufacture of a range of components with higher structural complexity and finer feature sizes that can be used to make chamber components to meet the design requirements of next generation technologies. As an example, the use of the corrosion and erosion resistant bonding materials disclosed herein provides the ability to bond structural members together while maintaining low particle generation, reduced contamination at wafer scale, and extended component assembly life required for semiconductor and MEMS processing applications. The materials and methods disclosed herein provide corrosion and erosion resistant bonded ceramic bodies and / or components with very high purity so that particles that may be released into the chamber will not be detrimental to semiconductor processing.
[0078] In one embodiment, a bonded ceramic body is disclosed herein, comprising: a first ceramic portion, the first ceramic portion comprising a first ceramic; a second ceramic portion, the second ceramic portion comprising a second ceramic, and a bonding layer formed between the first ceramic portion and the second ceramic portion. The bonding layer may have a thickness between 0.1 μm and 20 μm and contain silicon dioxide having a total impurity content of 20 ppm and less.
[0079] Depending on the application-specific requirements, the first ceramic portion and the second ceramic portion can be selected from the same ceramic or different ceramics. In an embodiment, the first ceramic portion and the second ceramic portion are selected from alumina, yttrium oxide, aluminum nitride, yttrium aluminum garnet (YAG; Y3Al5O 12 ), silicon carbide, mullite, quartz, SiAlON materials and combinations thereof. The materials selected for the first ceramic portion and the second ceramic portion may have suitably high corrosion and erosion resistance, material properties (such as thermal expansion coefficients) and purity acceptable for use as a bonded ceramic body as disclosed. Specific combinations of a bonding layer and a first ceramic portion and a second ceramic portion for making a bonded ceramic body are disclosed herein, however, embodiments of the bonded ceramic body other than those disclosed are possible.
[0080] The bonding layer may be composed of silicon dioxide or a combination of silicon dioxide, aluminum oxide and at least one rare earth oxide selected from the group consisting of: Y2O3, La2O3, CeO2, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Lu2O3. In a preferred embodiment, the rare earth oxide comprises yttrium oxide. The bonding layer made of silicon dioxide may have a very high purity, for example having a total purity of greater than 99.999%, preferably greater than 99.9995%, preferably 99.9999% relative to 100% pure silicon dioxide, which corresponds to impurity levels of 10ppm, 5ppm and 1ppm, respectively. The use of high purity silicon dioxide as disclosed provides very low (total < 5ppm) of alkali and / or alkaline earth bonding layer, which enhances halogen-based plasma resistance and reduces surface roughening and particle generation. As disclosed herein, the alkali and / or alkaline earth elements include Li, Na, K, Mg, Ca and Sr in a total combined amount of no more than 5ppm based on the weight of the bonding layer. Mg in the form of MgO is present in the bonding material in an amount of 2ppm and less relative to the total mass of the bonding material. For other embodiments as disclosed herein, the bonding layer may be formed of silicon dioxide, aluminum oxide and at least one rare earth oxide selected from the group consisting of Y2O3, La2O3, CeO2, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Lu2O3 and combinations of these, whereby the bonding layer has a purity of 99.995% and higher, preferably 99.998% and higher, preferably 99.999% and higher. The bonding layer as disclosed may include elements selected from the group consisting of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu and combinations thereof.
[0081] In some embodiments, the bonding layer may comprise an amorphous high purity (>99.999%) glass, and in alternative embodiments, it may comprise a high purity (>99.99%) glass ceramic comprising an amorphous glass phase or matrix and a crystalline phase dispersed in the matrix, wherein the crystalline ceramic phases are each formed in an amount between 5% and 99% by volume of the bonding layer, preferably between 5% and 90% by volume, preferably between 5% and 70% by volume, preferably between 10% and 60% by volume, preferably between 10% and 50% by volume. Either or both of the glass phase and the glass ceramic phase (comprising a glass phase and at least one crystalline ceramic phase) of the bonding layer may comprise at least one of the elements selected from the group consisting of: Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, and combinations thereof.
[0082] In embodiments, minimizing the thickness of the bonding layer may be beneficial, which may provide enhanced mechanical strength and improved plasma resistance. A bonded ceramic body is disclosed having a bonding layer having a thickness of 0.1 μm to 20 μm, preferably 0.1 μm to 15 μm, preferably 0.1 μm to 10 μm, preferably 0.1 μm to 5 μm, preferably 0.1 μm to 3 μm, preferably 1 μm to 8 μm, preferably 3 μm to 5 μm.
[0083] In the embodiments as disclosed, it may be beneficial to select a glass-ceramic bonding layer having a coefficient of thermal expansion (CTE) that is the same as or very close to the coefficient of thermal expansion (CTE) of the first ceramic portion and / or the second ceramic portion to minimize stress between the ceramic portion and / or the glass-ceramic bonding layer when heated, when cooled, and during use. This can prevent delamination or cracking of the ceramic body and / or the glass-ceramic bonding layer. The coefficient of thermal expansion of the glass-ceramic bonding layer can be adjusted for compatibility with the coefficient of thermal expansion of the ceramic portion by changing the relative amounts of silica, alumina, and at least one rare earth oxide (e.g., such as yttrium oxide) as disclosed herein. The glass-ceramic bonding layer as disclosed may have a CTE that is the same as the CTE of the ceramic portion (i.e., no difference) and is between 0 and 5% or from 0 to 10% of the ceramic portion in a temperature range of about 200°C to 1400°C.
[0084] The composition of the glass-ceramic bonding material can be selected to match the CTE of the substrate by, for example, 10% or less, through adjustment of the composition (of yttria, alumina, and silica). Silica has a CTE of about 0.5×10-6 / °C to 1×10-6 / °C, YAG has a CTE of 7×10-6 / °C to 8×10-6 / °C, and alumina has a CTE of 4×10-6 / °C to 5×10-6 / °C, and by changing their relative amounts, the CTE of the glass-ceramic bonding material can be modified.
[0085] A method for manufacturing a bonded ceramic body is disclosed. The method disclosed herein comprises the following steps:
[0086] a. The silicon dioxide powder is disposed between the surface of the first ceramic portion and the surface of the second ceramic portion to form a ceramic body component;
[0087] b. increasing the temperature of the ceramic body assembly to a sintering temperature of the silicon dioxide powder sufficient to bond the first ceramic portion and the second ceramic portion to form the bonded ceramic body; and
[0088] c. lowering the temperature of the bonded ceramic body,
[0089] Wherein the silicon dioxide has a specific surface area of at least 25 m2 / g measured by the BET method and a purity of 99.999% and higher, the method being characterized in that the method is carried out under conditions for preparing a joined ceramic body having the properties as disclosed in the preceding embodiments. The terms "surface area" and "specific surface area" are used interchangeably herein and refer to the surface area expressed in m2 / g.
[0090] The method disclosed herein includes step a: placing a powder of silicon dioxide between the surface of a first ceramic part and the surface of a second ceramic part to form a ceramic body component. The powder of silicon dioxide may have a specific surface area of 25 m2 / g and greater, preferably 30 m2 / g and greater, preferably between 25 and 50 m2 / g, preferably between 25 and 40 m2 / g as measured by the BET method as known in the art. Surface areas of silicon dioxide exceeding about 60 m2 / g and greater may adversely affect reaction kinetics. The specific surface area (SSA) of the starting powder was measured using a Horiba BET surface area analyzer model SA-9601, which is capable of measuring 0.01 to 2000 m2 / g for most samples with an accuracy of 10% and less. 2 / g specific surface area.
[0091] Although not required, it is preferred that the silica is a nanopowder having an average particle size between 20nm and 200nm, between 20nm and 150nm, between 20nm and 100nm, between 40 and 200, between 70nm and 200nm, between 100nm and 200nm, preferably between 30nm and 90nm, as measured by a laser particle size measurement method. The particle size of the starting powder is measured using a Horiba model LA-960 laser scattering particle size distribution analyzer capable of measuring particle sizes from 10nm to 5mm. The fine particle size associated with the silica nanopowder can produce agglomerates, which are loosely bound particles as defined herein, which can be broken down by applying shear or grinding forces applied during the mixing or grinding process. The silicon dioxide powder may have an average agglomerate size of between 0.75 μm and 3 μm, between 0.75 μm and 2.5 μm, between 0.75 μm and 2 μm, preferably between 1 μm and 2 μm. The silicon dioxide powder may have a d90 agglomerate size of between 4 μm and 6 μm, preferably between 4 μm and 5.5 μm, preferably between 4.5 μm and 5.5 μm.
[0092] The silicon dioxide powder forming the bonding layer has a very high purity, having a total purity of greater than 99.999%, preferably greater than 99.9995%, preferably 99.9999% and higher. These purity levels correspond to total impurity levels of 10 ppm, 5 ppm and 1 ppm, respectively. The total purity also includes alkali and alkaline earth elements and low melting temperature volatile metals, which are harmful to applications such as components in semiconductor processing chambers.
[0093] In order to achieve the sintering temperature reduced as disclosed, the silicon dioxide can be a nano powder in an embodiment. Nano powder as used herein is intended to mean a powder having a particle size between 20 μm and 200 μm in diameter and a specific surface area of 25 m2 / g and greater. The high purity of silicon dioxide also provides a bonding layer with very low (<5ppm) alkali and / or alkaline earth glass or glass ceramic composition and high bonding strength, thereby providing high resistance to halogen-based plasmas. The powder of silicon dioxide as disclosed herein also provides a very low (total <5ppm) transition metal content (including Fe, Co and Ni) and includes alkali and / or alkaline earth elements of Li, Na, K, Sr, Mg and Ca in an amount of less than 2ppm, preferably less than 1ppm each.
[0094] The combination of high purity, high surface area and fine particle size of silicon dioxide provides enhanced reactivity, thereby reducing the joining temperature and reducing the joining time without requiring applied pressure, although applied pressure can also be used if desired. The use of high purity silicon dioxide, preferably nanopowder with very small particle size and high surface area, reduces the activation energy required for sintering and thereby helps to reduce the sintering temperature of the joining material, as described in Vipin Kant Singh (1977) "Studies on the Sintering of Silicon Dioxide", Transactions of the Indian Ceramic Society, 36:1, 1-6, which is incorporated herein by reference. The activation energy as described therein can be calculated according to the Arrhenius equation:
[0095] K=A exp(-Q / RT)
[0096] Wherein K is a rate constant, Q is an activation energy, T is an absolute temperature, R is a universal gas constant, and A is another constant. The sintering temperature according to the embodiments disclosed herein may be between 1100°C and 1500°C, preferably between 1100°C and 1400°C, preferably between 1100°C and 1300°C, preferably between 1100°C and 1200°C, preferably between 1200°C and 1500°C, preferably between 1300°C and 1500°C, preferably between 1400°C and 1500°C, preferably between 1200°C and 1400°C.
[0097] In an embodiment, the silica powder of step a also comprises a powder of alumina and a powder of a rare earth oxide (e.g., yttria), wherein the alumina and yttria and / or the rare earth oxide each have a purity of 99.99% and higher. Without being bound by any particular theory, the dominant sintering mechanism for those high silica content (greater than 60% by weight silica and up to and including 100% silica) bonding materials (also comprising alumina and yttria as disclosed herein) may be viscous phase sintering resulting from the viscous flow of the highly reactive silica combined with the high silica content composition to promote wetting of the ceramic part. The high surface area of the silica nanopowder as disclosed increases the reactivity of the powder and thereby reduces the sintering temperature, thereby allowing the high silica composition to be sintered within the temperature range of the method as disclosed. The use of silica with a lower surface area and larger particle size may require a higher sintering temperature in excess of 1600°C. The composition range of bonding materials containing high amounts of silica is in the range of Figure 8 are depicted as thick lines in the phase diagram. Figure 8Also depicted are liquidus temperatures at which the compositions of yttrium oxide, silica, and alumina can combine to form a liquid phase. Thus, some embodiments of the bonding material may include silica in an amount of 60% to 100% by weight, and the remainder may include a mixture of alumina in an amount of 25% to 50% by weight and yttrium oxide in an amount of 50% to 75% by weight. In some embodiments, within this composition range, crystalline ceramic phases of Y2Si2O7 and mullite (3Al2O3-2SiO2) may be formed dispersed in a silica-rich glass phase or matrix. In alternative embodiments, within this composition range, the starting crystalline materials of yttrium oxide and alumina may be dispersed in a silica-rich glass phase or matrix. The yttrium oxide, silica, alumina phase diagram according to H. Mao, M. Selleby, and M. Fabrichnaya (2008) provides guidance on the crystalline phases formed upon cooling to a eutectic point below the composition range of the powder mixture and plasma-resistant composition as disclosed herein. The eutectic point, as known to those skilled in the art, is defined as the point on a phase diagram where the maximum number of permissible phases are in equilibrium.
[0098] As known in the art, the d50 particle size is defined as the median particle size and represents the value at which half of the population lies above this point and half lies below this point. Similarly, 90% of the distribution is below the d90 particle size, and 10% of the population is below d10.
[0099] The d10 particle size of the yttrium oxide powder used as a starting material according to one embodiment of the present invention is preferably 1 μm to 7 μm, preferably 1 μm to 6 μm, preferably 1 μm to 5 μm, preferably 2 μm to 7 μm, preferably μm3 to 7 μm, preferably 4 μm to 7 μm, preferably 5 μm to 7 μm.
[0100] The d50 particle size of the yttrium oxide powder used as the starting material according to one embodiment of the present invention is preferably 3 μm to 11 μm, preferably 3 μm to 9.5 μm, preferably 3 μm to 8.5 μm, preferably 3 μm to 7.5 μm, preferably 4 μm to 11 μm, preferably 5 μm to 11 μm, preferably 6 μm to 11 μm, preferably 7 μm to 11 μm.
[0101] The d90 particle size of the yttrium oxide powder used as the starting material according to one embodiment of the present invention is preferably 6 μm to 20 μm, preferably 6 μm to 18 μm, preferably 6 μm to 16 μm, preferably 8 μm to 20 μm, preferably 10 μm to 20 μm, preferably 15 μm to 20 μm, preferably 8 μm to 18 μm, preferably 10 μm to 18 μm.
[0102] Yttrium oxide powders usually have a 1 to 12 m 2 / g, preferably 1 to 9m2 / g, preferably 1 to 6m 2 / g, preferably 1 to 4 m 2 / g, preferably 2 to 9m 2 / g, preferably 2 to 6m 2 / g, preferably 2 to 4 m 2 / g specific surface area (SSA).
[0103] The purity of the yttrium oxide starting material is preferably higher than 99.99%, preferably higher than 99.995%, preferably higher than 99.999%, more preferably higher than 99.9995% and more preferably higher than 99.9999%. This corresponds to impurity levels of 100 ppm and less, preferably 50 ppm and less, preferably 25 ppm and less, preferably 10 ppm and less, more preferably about 1 ppm, preferably 1 ppm to 100 ppm, preferably 1 ppm to 50 ppm, preferably 1 ppm to 25 ppm, preferably 1 ppm to 10 ppm, preferably 1 ppm to 5 ppm, each relative to the total mass of the yttrium oxide starting material. The d10 particle size of the aluminum oxide powder used as a starting material according to one embodiment of the present invention is preferably 0.05μm to 4μm, preferably 0.05μm to 3μm, preferably 0.05μm to 2μm, preferably 0.05μm to 1μm, preferably 0.05μm to 0.75μm, preferably 0.05μm to 0.5μm, preferably 0.2μm to 4μm, preferably 0.2μm to 3μm, preferably 0.2μm to 2μm, preferably 0.2μm to 1μm, preferably 0.4μm to 4μm, preferably 0.4μm to 3μm, preferably 0.4μm to 2μm, preferably 0.4μm to 1μm, preferably 0.75μm to 2μm, preferably 0.75μm to 3μm, preferably 1μm to 3μm, preferably 2μm to 3μm.
[0104] The d50 particle size of the aluminum oxide powder used as the starting material according to one embodiment of the present invention is generally 0.15 μm to 8 μm, preferably 0.15 μm to 5 μm, preferably 0.15 μm to 3 μm, preferably 0.15 μm to 1 μm, preferably 0.15 μm to 0.5 μm, preferably 1 μm to 8 μm, preferably 1 μm to 6 μm, preferably 1 μm to 4 μm, preferably 2 μm to 6 μm, preferably 3 μm to 8 μm, preferably 4 μm to 8 μm, preferably 5 μm to 8 μm, preferably 3.5 μm to 6.5 μm.
[0105] The d90 particle size of the aluminum oxide powder used as a starting material according to one embodiment of the present invention is 0.35 μm to 60 μm, preferably 0.35 μm to 10 μm, preferably 0.35 μm to 5 μm, preferably 0.35 μm to 3 μm, preferably 0.35 μm to 1 μm, preferably 0.35 μm to 0.75 μm, preferably 3 μm to 80 μm, preferably 3 μm to 60 μm, preferably 3 μm to 40 μm, preferably 3 μm to 20 μm, preferably 10 μm to 60 μm, preferably 10 μm to 40 μm, preferably 10 μm to 30 μm, preferably 10 μm to 20 μm, preferably 30 μm to 60 μm, preferably 15 μm to 60 μm, preferably 40 μm to 60 μm, preferably 6 μm to 15 μm.
[0106] Alumina powders usually have a range of 3 to 18 μm 2 / g, preferably 3 to 16m 2 / g, preferably 3 to 14m 2 / g, preferably 3 to 12m 2 / g, preferably 3 to 10m 2 / g, preferably 3 to 6m 2 / g, preferably 6 to 18m 2 / g, preferably 6 to 14m 2 / g, preferably 8 to 18m 2 / g, preferably 10 to 18m 2 / g, preferably 8 to 10m 2 / g, preferably 4 to 9m 2 / g, preferably 5 to 10m 2 / g, preferably 6 to 8m 2 / g specific surface area.
[0107] As measured using the ICPMS method, the purity of the alumina starting material is typically higher than 99.99%, preferably higher than 99.995%, preferably higher than 99.999%, preferably higher than 99.9995%. Correspondingly, the total impurity content of the alumina powder may be 100 ppm and less, preferably 50 ppm and less, preferably 25 ppm, preferably 10 ppm and less, more preferably 5 ppm and less, each relative to the total mass of the alumina starting material.
[0108] The composite oxide powder mixture of more than one powder is hereinafter referred to as a bonding material, which comprises a combination of silicon dioxide, aluminum oxide and at least one rare earth oxide selected from the group consisting of Y2O3, La2O3, CeO2, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Lu2O3 and combinations thereof as disclosed herein. In a preferred embodiment, the rare earth oxide comprises yttrium oxide having powder characteristics as disclosed herein.
[0109] The total purity also includes alkali and alkaline earth elements and low melting temperature volatile metals which are deleterious to use in semiconductor processing chambers.
[0110] In an embodiment, step a of the method for forming a joined ceramic body may further include providing a powder of at least one rare earth oxide selected from the group consisting of Y2O3, La2O3, CeO2, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Lu2O3 and combinations thereof, wherein each of the rare earth oxides has a purity of 99.99% and higher.
[0111] The rare earth oxide selected from the group consisting of Y2O3, La2O3, CeO2, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Lu2O3 and combinations of these may have a surface area measured by the BET method as known to those skilled in the art, which surface area may be at least 2m2 / g, preferably at least 4m2 / g, preferably at least 6m2 / g, from 2 to 10m2 / gm, preferably between 4m2 / g and 8m2 / g.
[0112] The group of rare earth oxides as disclosed herein may have an average particle size distribution between 2 μm and 15 μm, preferably between 3 μm and 10 μm, preferably between 4 μm and 8 μm, measured using laser granulometry methods as known in the art.
[0113] The group of rare earth oxides as disclosed herein may have a total purity of higher than 99.99%, preferably higher than 99.995%, preferably higher than 99.999%, relative to 100% of the purity of the composite oxide. These purity levels correspond to total impurity levels of 100 ppm, 50 ppm and 10 ppm, respectively. The total purity also includes alkali and alkaline earth elements and low melting temperature volatile metals, which are harmful for use in semiconductor processing chambers.
[0114] The selection of silicon dioxide and metal oxide powders and their relative amounts depends on the product specific application requirements and the desired properties of the bonding layer formed by the bonding material during the sintering process as disclosed herein. The selection of bonding materials depends on the required plasma resistance and specific material properties (such as thermal expansion coefficient). The examples disclosed herein use bonding materials of a combination of silicon dioxide (SiO2) and silicon dioxide (SiO2), aluminum oxide (Al2O3) and rare earth oxides (e.g., yttrium oxide (Y2O3)). The silicon dioxide powder is preferably a nanopowder. However, any number of other rare earth oxides can be used in different amounts. As an example and not limitation, the rare earth oxide can be selected from the group consisting of the following items: Y2O3, La2O3, CeO2, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Lu2O3 and combinations of these. The bonding layer formed from the starting powders can be a glass or glass ceramic. Dopants or additives can be incorporated into the bonding layer to achieve the specific desired properties they provide therein. All starting powders (and rare earth oxides or dopants, where applicable) have a purity of at least 99.99% and higher and are free of fluorides and oxyfluorides. Table 1 lists the properties of composite oxide powders that can be used as bonding materials for forming bonding layers as disclosed herein.
[0115]
[0116] *Indicates the average aggregate size
[0117] Step a of the method also includes mixing, blending, grinding the bonding material or suspending it in a suspension medium as needed to prepare the bonding material for step b. In an embodiment, the bonding material can be in the form of a powder mixture of silicon dioxide (preferably nanopowder), aluminum oxide, yttrium oxide and / or the aforementioned composite oxide. In an alternative embodiment, the powder mixture can be in the form of a paste containing the aforementioned bonding material powder and a suspension medium (such as, for example, a solvent of water, ethanol, isopropanol, glycerol and a combination thereof) to form a plasma-resistant composition. In addition, an optional dopant can be added to any of the aforementioned forms of bonding materials and / or plasma-resistant compositions. The plasma-resistant composition includes a paste containing a powder mixture between 10% and 50% by volume, a powder mixture between 20% and 50% by volume, and preferably a powder mixture between 30% and 50% by volume. The selection of one or more mixing methods and the suspension medium (if used) and its amount depends on the method selected for applying the bonding material or plasma-resistant composition to the surface of the ceramic part. The method for mixing, blending or grinding is disclosed below and can be used to combine the powders into a powder mixture. To combine the powders to form the bonding material and / or plasma-resistant composition, the disclosed powders may be mixed according to the processes of vertical (tumbling) drum mixing, high energy ball milling or jet milling, as known in the art and without limitation. Ball milling and drum mixing may be done dry or wet, in which case the milling may be performed in a liquid medium such as a solvent or water-based system as previously mentioned or using only the powder mixture with or without grinding media. Any of the aforementioned milling processes may use high purity media, such as 99.99% and / or 99.995% pure aluminum oxide, to maintain the purity of the starting oxide powder, wherein the weight loading of the grinding media is 20% to 80% of the weight of the powder. The mixing process as disclosed is used to maintain the purity of the bonding material and / or plasma-resistant composition after mixing and may be repeated as needed to obtain the desired result. Preferred are plasma-resistant compositions or bonding materials having a maximum particle size (d100) of 4 μm to 6 μm, preferably 4 μm to 5 μm, more preferably 4 μm and less. As used herein, the plasma resistant composition may be composed of the same or similar powder as the bonding material, to which a suspending medium as disclosed herein is added to form the plasma resistant composition in the form of a paste. The plasma resistant composition as disclosed herein is one embodiment of the bonding material.
[0118] Step a of the method further comprises placing silicon dioxide (or a plasma resistant composition or a bonding material, as the case may be) between the first ceramic portion and the second ceramic portion to form a ceramic body assembly. The selected bonding material (or plasma resistant composition) can be applied between the surfaces of various ceramic substrates capable of withstanding the bonding temperatures disclosed herein to form a glass or glass-ceramic bonding layer between the ceramic portions. The properties of the glass or glass-ceramic bonding layer can be determined by the composition of the selected bonding material and its characteristics, the method of mixing before forming the bonding layer, the heat treatment during sintering and cooling, and other techniques known to those skilled in the art.
[0119] For the embodiments disclosed herein, silica powder (or bonding material or plasma-resistant composition, as the case may be) may be applied to the surface of the first ceramic part. The application of bonding material in powder form may be accomplished by sprinkling or spraying a powder mixture containing bonding material on the surface of the first ceramic part. As known to those skilled in the art, the application of bonding material or plasma-resistant composition in a suspension medium (in an amount required to form a paste or slurry from the suspension medium and powder) may be accomplished by brushing, spraying, dipping, spin coating, screen printing, etc. Thereafter, the surface of the second ceramic part is contacted with a layer of bonding material or plasma-resistant composition to form a ceramic body assembly. As an example and not limitation, a bonding material or plasma-resistant composition is applied over the surface of a substrate to bond as disclosed above. The application method must be compatible with the properties of the bonding material or plasma-resistant composition. A preferred embodiment utilizes a paste or slurry to set the oxide powder between the surfaces of the ceramic parts.
[0120] The ceramic part can be selected from a variety of materials, such as Al2O3, AlN, SiAlON, SiC, Y2O3, yttrium aluminum garnet (YAG, Y3Al5O 12), mullite, and combinations thereof. The choice of substrate material may be made based on resistance to halogen-based plasmas, mechanical strength, thermal conductivity, dielectric breakdown strength, CTE matching (within 0 to 10%) with a bonding layer, etc. As a non-limiting example, a bonding material may be placed between two similar materials with different electrical properties (such as a ceramic portion of a first resistivity and a ceramic portion of a second resistivity) to provide a high strength, plasma resistant bond between the two regions while maintaining the corrosion resistance provided by the alumina ceramic portion. The ceramic portion as disclosed herein may have a purity of at least 99.99% and higher, preferably 99.995% and higher, preferably 99.999% and higher. U.S. Provisional Patent Application No. 62 / 829,720, entitled "Controlled Porosity Yttrium Oxide for Etch Applications," and U.S. Provisional Patent Application No. 62 / 936821, entitled "Ceramic Sintered Body for Corrosion Resistant Components," disclose yttrium oxide and yttrium aluminum garnet (YAG) with a purity of from greater than 99.99% to 99.999% relative to 100% purity, both of which are incorporated herein by reference in their entirety. As an example, the following Table A provides the purity of an exemplary powder mixture (processed in batches in an amount to form a YAG phase, i.e., Y3Al5O12, when sintered) of a bonding material according to the present invention. An embodiment of an exemplary powder mixture to be used according to the present disclosure may be mixed with high purity silica from 25 wt % to 99 wt % as disclosed herein.
[0121] Table A
[0122]
[0123]
[0124] The ceramic body assembly may be placed in a heating furnace for bonding according to various heat profiles as disclosed herein. Fixtures and supports required to maintain contact between the substrates are used during the heat treatment as is familiar to those skilled in the art.
[0125] The method of manufacturing a bonded ceramic body disclosed herein includes step b of increasing the temperature of the ceramic body assembly to a sintering temperature of silicon dioxide powder sufficient to bond the first ceramic portion and the second ceramic portion to form the bonded ceramic body.
[0126] In an embodiment, sintering the silica powder and / or bonding material as disclosed herein to form a bonding layer for a bonding ceramic body can be achieved by directly sintering the silica powder or powder mixture of the bonding material in situ. This in-situ sintering of the bonding layer from the starting oxide powder maintains the purity of the starting material, thereby transferring them to the bonding layer. Known in the art is a process of first forming or sintering glass or glass ceramics, then grinding them into powder form, introducing impurities and contaminants into the glass or glass ceramics and thereby introducing them into the bonding layer. The ceramic body assembly of step b can be heated in a heating furnace at a temperature and duration sufficient to sinter the powder of the silica and / or bonding material comprising step a) to form a bonding ceramic body.
[0127] Joining or sintering the ceramic body components to form a joined ceramic body may be performed at a sintering temperature between 1100° C. and 1500° C., preferably between 1100° C. and 1400° C., preferably between 1100° C. and 1300° C., preferably between 1100° C. and 1200° C., preferably between 1200° C. and 1500° C., preferably between 1300° C. and 1500° C., preferably between 1400° C. and 1500° C., preferably between 1200° C. and 1400° C. Joining the ceramic body components may be performed at a sintering time between 1 hour and 8 hours, preferably between 1 hour and 6 hours, preferably between 1 hour and 4 hours, preferably between 6 hours and 8 hours, preferably between 4 hours and 8 hours, preferably between 3 hours and 5 hours. The heating rate may be between 1°C / min and 20°C / min, between 1°C / min and 10°C / min, and the cooling rate may be between 0.5°C / min and 20°C / min, preferably between 0.75°C / min and 15°C / min, preferably between 1°C / min and 10°C / min. The sintering process converts the bonding material into a bonding layer as disclosed. The ceramic body assembly is sintered at ambient pressure and atmospheric conditions.
[0128] Figure 1A bonded ceramic body according to the disclosed embodiments is depicted, wherein a first ceramic portion 9 and a second ceramic portion 11, respectively, may be bonded using a glass or glass ceramic based bonding layer 10 comprising silica, alumina, and in embodiments, a rare earth oxide, such as a rare earth oxide selected from the group consisting of: Y2O3, Ia2O3, CeO2, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Ho2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Lu2O3, and combinations thereof. The silica and / or bonding material that forms the bonding layer upon sintering may be dispersed in a suspension medium to form a paste ranging from about 5% to 50% by volume, preferably between 10% and 50% by volume, between 20% and 50% by volume of the paste, preferably between 30% and 50% by volume of the paste. In embodiments, the bonding material may have a maximum particle size of 6 μm and less. A bonding thickness 12 of 0.5 μm to 20 μm, preferably 0.5 μm to 15 μm, preferably 0.5 μm to 10 μm, preferably 0.5 μm to 6 μm, preferably 1 μm to 15 μm, preferably 3 μm to 10 μm, more preferably 4 μm to 8 μm may be achieved, however, other bonding thicknesses are contemplated depending on the characteristics of the starting bonding material, such as the composition of the bonding material and the ceramic part, the particle size distribution and the maximum particle or agglomerate size. Figure 1 As depicted in a and b, a reaction between ceramic parts 9 and 11 and bonding layer 10 is observed. The bonding layer 10 between the interfaces of ceramic parts 9 and 11 does not have a transition region and is uniform in the phase distribution throughout the thickness of the bonding layer. The bonding layer 10 may have a glass or glass ceramic phase uniformly distributed across the thickness between the ceramic parts, which does not contain fluorides or oxyfluorides. The transition region or zone as defined herein represents a region or zone formed near at least one ceramic part and within the bonding layer, which may be caused by a chemical reaction (between at least one ceramic part and the bonding layer) to form a region different in composition, crystal phase or other characteristics. Each of the bonding ceramic bodies, bonding layers, bonding materials and plasma-resistant compositions disclosed herein does not contain fluorides and / or oxyfluorides. Each of the bonding ceramic bodies, bonding layers, bonding materials and plasma-resistant compositions disclosed herein does not contain a transition region as defined herein.
[0129] Figure 2 A bonded ceramic body according to an embodiment as disclosed is shown, wherein a high purity (>99.999%) silica particulate material (such as Heraeus zandosil) dispersed in a 50% by volume aqueous paste is used. ) was used to bond ceramic parts composed of aluminum oxide at 1400°C for 4 hours. It is reported that the particles have a d50 particle size of 200μm to 250μm. A bond thickness 12 of about 35μm was measured and cracking was observed in the bonding layer 10. The large particle size of silicon dioxide and the significant difference in thermal expansion coefficient (greater than 10%) between the ceramic parts 9, 11 and the bonding layer 10 may cause cracking of the bonding layer. Tables 2 and 3 list the ceramic parts and various bonding materials that are combined to make the bonded ceramic body as disclosed. In some embodiments, the glass-ceramic bonding material used to form the bonding layer according to Table 3 can be a powder mixture as disclosed herein, which contains about 50% SiO2, about 29% Y2O3 and about 21% Al2O3 by weight. Depending on the choice of the ceramic part, other compositions and ratios of the bonding material can be used. In other embodiments, the glass ceramic bonding material may be composed of a powder mixture of about 40% SiO2, about 34% Y2O3, and about 26% Al2O3 by weight. In other embodiments, the bonding material comprises silicon dioxide in an amount of 25% by weight silicon dioxide to 99% by weight silicon dioxide, and the balance comprises a mixture of yttrium oxide and aluminum oxide in a ratio of 43% by weight aluminum oxide and 57% by weight yttrium oxide. Table 3 lists exemplary compositions of bonding materials comprising yttrium oxide, aluminum oxide, and silicon dioxide and conditions for forming a bonded ceramic body as disclosed herein.
[0130] Table 2 lists the properties of the glass bonding layer comprising silicon dioxide.
[0131]
[0132]
[0133] As a guide, provide Figure 8 1 to illustrate the ratios required to make bonding materials having different compositions comprising yttrium oxide, aluminum oxide, and silicon dioxide. Yttrium oxide and aluminum oxide are batch processed in a ratio to form a YAG phase in combination with 25 wt % to 99 wt % silicon dioxide, and in other embodiments, bonding materials as disclosed herein may comprise 100 wt % silicon dioxide (e.g., Figure 8 A typical bonding material composition disclosed herein has aluminum oxide and yttrium oxide in a ratio to form YAG upon sintering (about 43 wt.% aluminum oxide and about 57 wt.% yttrium oxide) combined with silicon dioxide in an amount of 25 wt.% to a maximum of 99 wt.% silicon dioxide, and the balance is a mixture of yttrium oxide and aluminum oxide (processed in batches to form YAG) in a combined amount of 1% to 75% based on the total weight of the bonding material. In other embodiments as disclosed herein, the bonding material may include 100% silicon dioxide.
[0134] Although the embodiments and examples disclosed herein are performed at ambient pressure and do not require the use of external pressure, if desired, an externally applied pressure between 0.01 MPa and 1.4 MPa, preferably between 0.01 MPa and 0.7 MPa, preferably between 0.01 M and 0.35 M, preferably between 0.01 MPa and 0.14 MPa, preferably between 0.01 MPa and 0.07 MPa may be used.
[0135] In an embodiment, the sintering curve can be adjusted to a temperature and time sufficient to permit the formation of a glass-ceramic bonding layer formed in situ between the surfaces of the ceramic substrates from the powder bonding mixture. The resulting properties and composition of the glass-ceramic bonding layer will be determined by the powder mixture composition, the substrate material, and the thermal profile (particularly the cooling rate) used during the bonding process to allow crystallization of the bonding material upon cooling. An exemplary cooling rate to minimize thermal stress is 0.5°C / minute to 5°C / minute, depending on the thermal mass / part size.
[0136] Figure 3 Differential Scanning Calorimetry (DSC) results as performed in the art for a bonding material comprising powders of yttria, silica, and alumina for forming a glass-ceramic bonding layer according to embodiments as disclosed herein are shown. A Linseis model DSC PT 1600 was used for all measurements. Figure 3 An exothermic crystallization peak 13a is shown, which corresponds to the in situ crystallization of at least one crystalline ceramic phase from the joining material (according to Figure 8 In some embodiments, at least one crystalline ceramic phase may be selected from the group consisting of mullite, alumina, Y2Si2O7, Y2SiO5, and Y3Al5O12 (yttrium aluminum garnet, YAG). The YAG phase is preferably polycrystalline. The crystalline ceramic phase is formed from starting powders of silicon dioxide, yttrium oxide, and aluminum oxide by an in-situ reactive sintering process and dispersed in a silicon dioxide-rich glass phase or matrix to form a glass-ceramic bonding material. Figure 3 The endothermic "dip" indicated as 13b in the figure indicates melting to form at least one silica-rich glass liquid phase. Without being bound by any particular theory, bonding between the ceramic parts can be achieved by selecting a series of bonding material compositions that melt and form a silica-rich liquid phase at a temperature compatible with the temperature of the process, whereby the silica-rich liquid phase wets and bonds the surfaces of the ceramic parts during sintering. Figure 8The composition range of the bonding material formed by liquid phase sintering (at temperatures of 1100° C. to 1500° C. compatible with the method as disclosed) is depicted within the dashed area and includes 25% to 60% by weight silica, and the balance includes a mixture of 25% to 50% by weight alumina and 50% to 75% by weight yttria. Within this composition range, crystalline ceramic phases of mullite (3Al2O3-2SiO2), Y2Si2O7, alumina (Al2O3), Y3Al5O12 (YAG) and Y2SiO5 and combinations thereof may form. In an embodiment, at least one of these phases may be present in combination with an amorphous silica glass phase to form a glass ceramic. The yttria, silica, alumina phase diagram according to H. Mao, M. Selleby and M. Fabrichnaya (2008) provides guidance on crystalline phases formed from powder mixtures and plasma-resistant compositions of composition ranges as disclosed herein. Thus, an embodiment of the bonding material may include 25 to 60 wt% of silica, and the remainder includes a mixture of 25 to 50 wt% of alumina and 50 to 75 wt% of yttria. Within this composition range, at least one of the crystalline ceramic phases of mullite (3Al2O3-2SiO2), Y2Si2O7, alumina (Al2O3), Y3Al5O12 (YAG), and Y2SiO5, and combinations thereof, may be formed to be dispersed in a silica-rich glass phase or matrix.
[0137] The composition of the bonding material as disclosed herein generally comprises 25 to 99 weight percent silicon dioxide, and the balance comprises a mixture of 25 to 50 weight percent aluminum oxide and 50 to 75 weight percent yttrium oxide. In other embodiments, the bonding material may include a mixture of high purity silicon dioxide nanopowders (such as Heraeus zandosil 30 and 30 ) formed. Within this composition range, the bonding between the ceramic parts is achieved by liquid phase or viscous phase sintering of the bonding material and their combination. Therefore, no reaction is observed between the bonding material and the ceramic parts.
[0138] In situ crystallization of at least one ceramic phase from the bonding material during liquid phase sintering combined with the very high purity silica-rich glass phase provides a high purity, corrosion-resistant bonding layer (or bond line) between ceramic components that is resistant to the corrosive and aggressive effects of halogen-based plasmas when used during semiconductor processing.
[0139] Crystallization of the bonding material to form the glass-ceramic as disclosed herein can be observed at temperatures greater than 1000°C and 1400°C (as indicated by exothermic peak 13a), thus sintering temperatures of 1100°C to 1500°C are compatible with the disclosed method. Two measurements were performed, and Figure 3 The agreement between these two measurements is depicted in .
[0140] Depending on the composition of the bonding material, the heat treatment (particularly the cooling rate) and the presence of additives or dopants, the relative amounts of the silica-rich glass phase (the glass phase is an amorphous phase known to those skilled in the art) and the crystalline ceramic phase of the bonding layer may be different. The ceramic phase of the bonding layer may contain rare earth oxide elements selected from the group consisting of the following items: Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu and combinations thereof. For use as a bonding material in a semiconductor processing chamber, very high purity materials are required. Advantageously, the use of the bonding material as disclosed produces a high purity, alkali-free and / or alkaline earth-free glass or glass-ceramic composition with high bonding strength, which is resistant to halogen-based plasmas. In an embodiment, dopants can be used to enhance specific properties such as viscosity, resistivity, coefficient of thermal expansion, crystallinity in glass-ceramics, etc. of glass-ceramics during sintering. The high-purity bonding material composition as disclosed herein can bring about etching performance similar to or improved etching performance of commercially available structures used as semiconductor processing chamber components.
[0141] The method as disclosed herein includes step c of reducing the temperature of the bonded ceramic body. The relative amount of amorphous and crystalline phases present in the glass-ceramic bonding layer can be affected by the cooling rate during the period of reducing the temperature of the bonded ceramic body. Crystallization is a time-dependent process, whereby a higher cooling rate reduces the amount of time for crystallization to occur and can therefore result in a lower amount of crystalline phase and a correspondingly higher amount of amorphous phase in the glass-ceramic bonding layer. Therefore, a lower cooling rate can increase the amount of time for crystallization to occur and can therefore result in a higher amount of crystalline phase in the glass-ceramic bonding layer and can result in a correspondingly lower amount of amorphous phase in the glass-ceramic bonding layer. The heat treatment as disclosed herein can be modified to affect the amount of crystalline phase present in the glass-ceramic bonding layer. The amount of amorphous and crystalline phases may also be affected by other variables such as bonding material composition and particle size distribution, the presence of dopants, the purity level in the starting material, etc. A cooling rate between 0.5°C / minute and 20°C / minute, preferably between 0.75°C / minute and 15°C / minute, preferably between 1°C / minute and 10°C / minute can be used. Cooling can be performed under ambient conditions or in an embodiment under forced convection.
[0142] The method as disclosed herein optionally further comprises step d) machining the bonded ceramic body to produce a bonded ceramic body part for use in a semiconductor processing chamber. As known to those skilled in the art, machining may be performed to form a bonded ceramic body part from a bonded ceramic body as disclosed herein. Examples of these may be selected from the group consisting of dielectric windows or RF windows, rings, nozzles or gas injectors, showerheads, gas distribution plates, etching chamber liners, plasma source adapters, gas inlet adapters, diffusers, electronic wafer chucks, chucks, positioning plates, ion suppressor elements, panels and / or protective rings in etching chambers. The use of ceramic parts, composite oxide powders, bonding materials and methods as disclosed herein may be particularly suitable for preparing large bonded ceramic bodies, for example, with a diameter between 100 mm and 622 mm, as required for use in prior art semiconductor processing chambers. For example, in one embodiment, the bonded ceramic body may be formed into a disc shape with a diameter of 100 mm to 622 mm and a thickness across a range of 5 mm to 60 mm. In another embodiment, the bonded ceramic body may be formed into a disc shape with a diameter of 100 mm to 622 mm. In another embodiment, the joint ceramic body may be formed into a disc shape with a diameter of 100 mm to 406 mm. In other embodiments, the joint ceramic body may have a size of 200 mm to 622 mm, preferably 300 mm to 622 mm, preferably 350 mm to 622 mm, preferably 400 mm to 622 mm, more preferably 450 mm to 622 mm, more preferably 500 mm to 622 mm, more preferably 550 mm to 622 mm, respectively, relative to the longest dimension of the joint body. In the embodiment in which the joint ceramic body is formed into a disc shape, the longest extension constitutes the diameter.
[0143] like Figure 4 As shown, another embodiment of the technology disclosed herein may include a semiconductor processing system 9600, also referred to as a processing system. The processing system 9600 includes a vacuum chamber 9650, a vacuum source, and a chuck 9608, on which a wafer 50 (also represented as a semiconductor substrate) is supported. A showerhead 9700 forms an upper wall or is mounted below the upper wall of the vacuum chamber 9650. The ceramic showerhead 9700 includes a gas chamber in fluid communication with a plurality of showerhead gas outlets for supplying process gas to the interior of the vacuum chamber 9650. The showerhead 9700 is in fluid communication with a gas delivery system 9606. In addition, the showerhead 9700 may include a central opening configured to receive a central gas injector (also referred to as a nozzle) 9714. The RF energy source excites the process gas into a plasma state to process the semiconductor substrate. The flow rate of the process gas supplied by the central gas injector 9714 and the flow rate of the process gas supplied by the ceramic showerhead can be independently controlled. The showerhead 9700, gas delivery system 9606, and center gas injector 9714 may be made of a bonded ceramic body as disclosed herein.
[0144] The system 9600 may also include an electrostatic chuck 9608 designed to carry a wafer 50. The chuck 9608 may include a positioning plate 9609 for supporting the wafer 50. The positioning plate 9609 may be formed of a bonded ceramic body as disclosed herein and may have a clamping electrode disposed within the positioning plate near a supporting surface of the positioning plate 9609 to electrostatically hold the wafer 50 when disposed on the positioning plate 9609. The chuck 9608 may include a pedestal 9611 having a ring extending to support the positioning plate 9609, and a shaft 9610 disposed between the pedestal and the positioning plate to support the positioning plate above the pedestal so that a gap is formed between the positioning plate 9609 and the pedestal 9610, wherein the shaft 9610 supports the positioning plate near a peripheral edge of the positioning plate 9609. The chuck 9608 and the positioning plate 9609 may be made of a bonded ceramic body as disclosed herein.
[0145] Portions of the surface of showerhead 9700 may be covered with shield ring 9712. Portions of the surface of showerhead 9700, particularly radial sides of the surface of showerhead 9700, may be covered with upper shield ring 9710. Shield ring 9712 and upper shield ring 9710 may be made of a bonded ceramic body as disclosed herein.
[0146] Portions of the support surface of positioning disk 9609 may be covered with a cover ring 9614. Additional portions of the surface of positioning disk 9609 may be covered with a top shield ring 9612 and / or a shield ring 9613. Shield ring 9613, cover ring 9614, and top shield ring 9612 may be made of a bonded ceramic body as disclosed herein.
[0147] Figure 5 , a wafer support assembly is depicted, which includes a positioning plate 9609 and a cover ring 9614, the positioning plate can be at least a portion of an electronic wafer chuck or an electrostatic chuck (ESC), each cover ring can have a Fig. 6A , Figure 6B and Figure 7 Embedded features in the depicted cross-section 7 are such as lines, traces, webs, coil shapes, sheets, screens, etc.
[0148] Fig. 6A A plan view of a cover ring 9614 formed of a bonded ceramic body as disclosed is shown with an embedded element 8, which may be a wire, trace, mesh, screen, coil shape, wire mesh, etc. Other configurations and embodiments of embedded element 8 are within the scope of the present disclosure. Figure 6B It is shown that a ceramic body can be formed by bonding as disclosed and having Figure 7 A cross-sectional view of the cover ring 9614, top shield ring 9612, and shield ring 9613 of the embedded or laminated component is depicted.
[0149] Figure 7 A cross-sectional view of an exemplary bonded ceramic body is shown, the bonded ceramic body having: a top layer 2, which can be a dielectric layer; an electrode 3, which can be an embedded metal or resistive feature made of, for example, tungsten, platinum, molybdenum or niobium or other refractory noble metals; a resistive element 4, which can be made of a material having resistivity and other properties such as dielectric loss selected for compatibility with ceramic portions 5 and 6, for example, when ceramic portions 5 and 6 are alumina, the resistive element 4 can be a refractory or noble metal such as niobium, tungsten, molybdenum or platinum; wherein the elements 3 and 4 can be configured according to application specific requirements, and the ceramic regions 5 and 6 can include any number of ceramic portions as disclosed herein and their combinations. In a preferred embodiment, either of the ceramic regions 5 and / or 6 contains alumina and / or YAG. For example, the resistive element 4 can be arranged in a 2D or 3D configuration so that it can provide control over heating over the entire volume of the ceramic portion 5 or 6. The electrode 3 and / or the resistive element 4 can be formed on top of the ceramic portion by screen printing, stencil printing, jet deposition, and other methods known to those skilled in the art. Without limitation, the bonding layer 10 formed by the materials and methods disclosed herein can be disposed between the ceramic portions 5 and 6, and can also be disposed between the ceramic portion and the electrode 3 and the resistive element 4, as well as combinations thereof, to provide a plasma-resistant bond to form a bonded ceramic component from at least two ceramic portions. In a preferred embodiment, the bonding layer 10 is adjacent to the ceramic portions 5 and 6.
[0150] The properties of the bonded ceramic body parts, such as corrosion and erosion resistance, thermal expansion coefficient, thermal conductivity, and dielectric breakdown strength, can be at least partially determined by the material selected to form the bonding layer. The use of high-purity silicon dioxide and bonding materials as disclosed herein forms a glass or glass-ceramic bonding layer that provides a high-strength bond between ceramic parts while maintaining resistance to halogen-based plasmas. The aforementioned properties of the bonded ceramic body and / or parts may also be affected by the thickness of the bonding layer. Minimizing the thickness of the layer can provide improved resistance to plasma erosion and corrosion during use and reduce stress within the layer. Therefore, it is desirable to have a bonding thickness of, for example, between 0.5 μm and 20 μm, between 0.5 μm and 15 μm, between 0.5 μm and 10 μm, between 0.5 μm and 6 μm, preferably 1 μm to 15 μm, preferably 3 μm to 10 μm, and more preferably 4 μm to 8 μm. The bonding layer enables the manufacture of ceramic bodies and parts from a wide range of materials that can support higher design complexity. As an example, Figure 5A wafer support assembly is depicted having a positioning plate 9609, which may be part of a chuck or electronic wafer chuck or electrostatic chuck (ESC), and a cover ring 9614. The positioning plate and / or cover ring may have multiple layers and embedded materials, such as in Figure 7 The cross section is shown in 7.
[0151] Exemplary embodiments :
[0152] For all examples, high purity silica nanopowders such as Heraeus 30 and zandosil All examples were performed at ambient pressure.
[0153] For Examples 1 to 4, the bonding material selected for evaluation contained a composite oxide of 50% silica, 21.5% alumina and 28.5% yttrium oxide by weight. For Examples 1 to 5, 7 and 9, high purity silica as disclosed herein was used to bond the ceramic parts. Examples 1 to 4 are illustrative of the use of composite oxide powders and silica powders as disclosed to bond ceramic parts. All starting powders have a purity of at least 99.99% and higher and are free of fluorides and oxyfluorides. The properties of the starting powders are listed in Table 1. According to an embodiment of the example, a bonding layer comprising pure silica (formed by silica nanopowder) forms an amorphous glass phase as known to those skilled in the art.
[0154] The bonding material as disclosed was dispersed in an aqueous suspension medium at 40% to 50% solid loading. The samples were sintered at different temperatures and times as disclosed below. In all embodiments as disclosed herein, no transition region was observed. A transition region or zone as defined herein represents a region or zone formed between the interface of at least one ceramic part proximal to the ceramic part within the bonding layer by a chemical reaction between the two ceramic parts to form a zone or zone that is different in composition, crystal phase or other characteristics.
[0155] Example 1 : A joined ceramic body is formed of a joining material comprising alumina, yttrium oxide, and silicon dioxide, each having a purity, particle size distribution, and surface area as disclosed herein (see Table 1), prepared in a 40 volume % aqueous paste, ball milled using high purity (>99.99%) alumina media, and disposed between ceramic parts made of alumina having a purity of at least 99.99% and greater to form a ceramic body assembly. The composition of the joining material is as disclosed in Table 3. The ceramic body assembly is sintered in air at ambient pressure at a sintering temperature of 1400° C. for 4 hours to form a joined ceramic body. Upon in situ reactive sintering, the joining material forms a glass ceramic, as described in accordance with Figure 3The DSC results (as measured according to ASTM D3418) are depicted. The glass-ceramic comprises at least one crystalline ceramic phase selected from the group consisting of mullite, alumina, Y2Si2O7, Y2SiO5, Y3Al5O12 (yttrium aluminum garnet, or YAG) (phase diagram according to H. Mao, M. Selleby and M. Fabrichnaya (2008)), wherein the crystalline ceramic phase is dispersed in a glass amorphous matrix comprising silicon dioxide. The bonding layer has a bonding thickness between 2 μm and 5 μm and achieves an acceptable bond between the ceramic parts (i.e., a monolithic body is achieved after sintering). It was observed that the bonding layer was uniform across the thickness between the ceramic parts and had no cracks or fissures. This is Figure 1 a) depicted at 500x magnification and b) depicted at 5000x magnification. Figure 1 As demonstrated by a and b, no reaction between the ceramic parts and the bonding material is observed. The bonding layer formed between the interfaces of the alumina parts does not have a transition zone and is uniform over the entire phase distribution. The bonding layer comprises a glass ceramic that does not contain fluorides and / or oxyfluorides. Therefore, a bonding ceramic body is disclosed herein that does not contain or is substantially free of fluorides and / or oxyfluorides. In an alternative embodiment, when a nanopowder of silicon dioxide powder having the surface area, purity and particle size characteristics as disclosed in Example 5 is arranged between the ceramic parts and sintered according to this embodiment, an acceptable bond between the ceramic parts is also achieved.
[0156] Example 2 : A joined ceramic body is formed of a glass-ceramic joining material as disclosed in Example 1, which is disposed between surfaces of ceramic parts made of alumina as in Example 1 to form a ceramic body assembly. The ceramic body assembly is sintered at 1200° C. for 4 hours in air at ambient pressure to form a joined ceramic body. A glass-ceramic joining layer containing a phase as disclosed according to Example 1 is formed. An acceptable bond between the ceramic parts is achieved using a joining material as disclosed herein. In an alternative embodiment, an acceptable bond between the ceramic parts is also achieved when a nanopowder of silicon dioxide having the surface area, purity and particle size characteristics as disclosed herein is disposed between the ceramic parts according to this embodiment and sintered.
[0157] Example 3: A joined ceramic body was formed of a glass-ceramic joining material as disclosed in Example 1, disposed between ceramic parts made of alumina as disclosed in Example 1 to form a ceramic body assembly. The ceramic body assembly was sintered at 1000°C for 8 hours in air at ambient pressure to form a joined ceramic body. Debonding of the ceramic sintered body was observed due to insufficient bonding between the ceramic parts and the joining material. Debonding of the ceramic sintered body was also observed when a silica powder having the surface area, purity and particle size characteristics as disclosed herein was disposed between the ceramic parts due to insufficient bonding between the ceramic parts and the joining material. The temperature of 1000°C was too low for proper bonding, and debonding of the body was observed.
[0158] Example 4 : A joined ceramic body is formed of a joining material as disclosed in Example 1, disposed between ceramic parts made of aluminum oxide and yttrium oxide, each having a purity of at least 99.99% and higher, to form a ceramic body assembly. The ceramic body assembly is sintered at 1400° C. for 4 hours in air at ambient pressure to form a joined ceramic body. Due to insufficient bonding between the yttrium oxide ceramic part and the joining material, detachment of the ceramic sintered body is observed at the yttrium oxide / joining material interface.
[0159] Example 5 :Joint ceramic bodies are formed of silica nanopowders having a purity of at least 99.999% and higher, a surface area between 25m2 / g and 40m2 / g, and an average particle size between 20nm and 200nm as disclosed herein. The powder is dispersed in an aqueous suspension medium at about 50% volume loading and disposed between ceramic parts made of alumina and yttrium oxide, each having a purity of at least 99.99% and higher, to form a ceramic body assembly. The ceramic body assembly is sintered at 1400°C for 4 hours in air at ambient pressure to form a joined ceramic body. Acceptable bonding between ceramic parts is achieved using silica powder as disclosed herein.
[0160] Example 6 : The bonded ceramic body according to the disclosed materials and methods is made of an alumina ceramic portion having a purity of at least 99.99% and higher to form a ceramic body component. In this embodiment, a high purity (>99.999%) granular SiO2 powder (such as Heraeus zandosil) having an average (d50) agglomerate size of 200 μm to 250 μm is used. ) to form a bonding layer. The silica particles are dispersed in a 50 volume % aqueous paste. The ceramic body assembly is sintered at 1400° C. for 4 hours in air at ambient pressure to form a bonded ceramic body. A bonding thickness of 35 μm is obtained, as shown in Figure 2Depicted in a) at 500x magnification and b) at 5000x magnification. Despite bonding between the ceramic part and the silica layer, significant cracking was observed in the bonding layer. Greater stresses may be placed on the thicker, predominantly or completely glass-bonded layer depending on the thermal expansion characteristics of the ceramic part, thereby exacerbating the observed cracking. Finer particle sizes of the silica powder (such as those of typical nanopowders) and reduced bonding thickness (less than 35 μm) may increase the strength of the bonding layer, thereby mitigating the observed cracking.
[0161] Example 7 : A joined ceramic body is formed of a silicon dioxide powder having a purity of at least 99.999% and higher, a surface area between 25 m2 / g and 40 m2 / g, and an average particle size between 20 nm and 200 nm as disclosed herein, disposed between ceramic parts made of yttria having a purity of at least 99.99% and higher to form a ceramic body assembly. The ceramic body assembly is sintered at 1400° C. for 4 hours in air at ambient pressure to form a joined ceramic body. An acceptable bond between the yttria ceramic parts is achieved using silicon dioxide powder as disclosed herein.
[0162] Example 8 The bonding ceramic body is formed of a silicon dioxide nanopowder having a purity of at least 99.999% and higher as disclosed herein, a surface area between 25 m2 / g and 50 m2 / g and an average particle size between 20 nm and 200 nm (as measured by BET), disposed in an yttrium aluminum garnet structure (YAG, Y3Al5O 12 ) between ceramic parts made of to form a ceramic body assembly. The ceramic body assembly is sintered at 1400° C. for 4 hours in air at ambient pressure to form a joined ceramic body. Silica powder as disclosed herein is used to achieve acceptable bonding between ceramic parts.
[0163] Tables 2 and 3 summarize joined ceramic bodies according to embodiments as disclosed herein.
[0164] Reference numerals list
[0165] picture Reference numerals describe 7 2 Top floor 7 3 electrode 7 4 Resistor 7 5 Ceramic parts 7 6 Ceramic parts 4、5、6B、7 7 cross section 6A 8 Embedded components 1、2 9、11 Ceramic parts 1、2 10 Bonding layer 1、2 12 Combination thickness 3 13 Exothermic peak 4、5 50 Chip 4 9600 Semiconductor processing systems 4 9606 Gas delivery systems 4 9608 Suction cup 4、5 9609 Positioning plate 4 9610 axis 4 9611 Base 4、6B 9612 Top shielding ring 4、6B 9613 Shielding ring 4, 5, 6A, 6B 9614 Cover Ring 4 9700 Nozzle 4 9710 Upper shielding ring 4 9712 Shielding ring 4 9714 Center Gas Injector 4 9650 Vacuum Chamber
[0166] Example 9:The joined ceramic body is formed by a joining material comprising 50 wt% silica, 21.5 wt% alumina and 28.5 wt% yttrium oxide. Silica, alumina and yttrium oxide have powder properties according to the disclosure in Table 1. The joining material has a purity of at least 99.99% and higher, and is dispersed in water in an amount of about 40 wt% solid to form a paste and is disposed between ceramic parts made of alumina having a purity of at least 99.99% and higher, thereby forming a ceramic body assembly. The ceramic body assembly is sintered at 1400° C. in air at ambient pressure for 1 hour to form a joined ceramic body. During sintering, a glass-ceramic joining layer having a thickness of about 10 μm is formed by an in-situ sintering reaction to form a glass-ceramic comprising an amorphous silica-rich glass phase according to the phase disclosed in Example 1 and at least one crystalline ceramic phase. An acceptable bond between the alumina ceramic parts is achieved.
[0167] Example 10 :A joined ceramic body is formed of a joining material comprising 50 wt % silica, 21.5 wt % alumina and 28.5 wt % yttrium oxide. The silica, alumina and yttrium oxide have properties according to the disclosure in Table 1. The joining material has a purity of at least 99.99% and higher, and is dispersed in water in an amount of about 50 wt % solids and disposed between ceramic parts made of alumina having a purity of at least 99.99% and higher, thereby forming a ceramic body assembly. The ceramic body assembly is sintered at 1500° C. in air at ambient pressure for 1 hour to form a joined ceramic body. During sintering, a glass-ceramic joining layer having a thickness of from 5 μm to 10 μm is formed by an in-situ reaction to form an amorphous silica-rich glass phase and at least one crystalline ceramic phase according to Example 1. An acceptable bond between the alumina ceramic parts is achieved.
[0168] A number of embodiments of the present invention have been disclosed. However, it should be understood that various modifications may be made without departing from the spirit and scope of the embodiments of the present invention. Therefore, other embodiments are within the scope of the present invention.
Claims
1. A bonded ceramic body, comprising: a first ceramic portion, the first ceramic portion comprising a first ceramic; b. a second ceramic portion, wherein the second ceramic portion comprises a second ceramic; c. a bonding layer formed between the first ceramic portion and the second ceramic portion, The bonding layer has a combined thickness of 0.5 μm to 20 μm, and comprises silicon dioxide, or a combination of silicon dioxide, aluminum oxide, and at least one rare earth oxide selected from the group consisting of Y2O3, La2O3, CeO2, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Lu2O3; wherein the bonding layer has a total purity of 99.999% and higher relative to 100% purity. 2 . The joined ceramic body according to claim 1 , wherein the joining layer contains an amorphous glass phase having a total impurity content of 10 ppm and less relative to the mass of the joining layer. 3 . The joined ceramic body according to claim 1 , wherein the joining layer comprises a glass-ceramic comprising an amorphous glass phase and at least one crystalline ceramic phase. 4 . The joined ceramic body according to claim 1 , wherein the joining layer comprises at least one crystalline ceramic phase having a crystallinity in an amount of 5% to 99% by volume of the joining layer.
5. The bonded ceramic body according to claim 3, wherein the at least one crystalline ceramic phase comprises at least one selected from the group consisting of mullite, alumina, Y2Si2O7, Y2SiO5, and Y3Al5O 12 (Yttrium aluminum garnet).
6. The bonded ceramic body according to claim 5, wherein the Y3Al5O 12 (Yttrium aluminum garnet) is polycrystalline. 7 . The joined ceramic body according to claim 1 , wherein the joining layer has a total impurity content of 5 ppm and less relative to the mass of the joining layer. 8 . The joined ceramic body according to claim 1 , wherein the joining layer has a total alkali or alkaline earth element content of 5 ppm and less relative to the mass of the joining layer. 9 . The joined ceramic body according to claim 1 , wherein the joining layer has a bonding thickness of 1 μm to 15 μm.
10. The joined ceramic body according to claim 1 or 2, wherein the joining layer further comprises an element selected from the group consisting of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu and combinations thereof.
11. The joined ceramic body according to claim 1 or 2, wherein the first ceramic portion and the second ceramic portion comprise the same ceramic. 12 . The joined ceramic body according to claim 1 , wherein the first ceramic and the second ceramic comprise different ceramics.
13. The jointed ceramic body according to claim 1 or 2, wherein each of the first ceramic portion and the second ceramic portion is selected from the group consisting of aluminum oxide, yttrium oxide, aluminum nitride, yttrium aluminum garnet (YAG; Y3Al5O 12 ), silicon carbide, quartz, mullite, SiAlON materials and combinations thereof.
14. The joined ceramic body according to the preceding claim 11, wherein the first ceramic portion and the second ceramic portion are alumina.
15. The joined ceramic body according to claim 1 or 2, wherein the joining layer has a coefficient of thermal expansion (CTE) of 0% to 10% of each of the first ceramic portion and the second ceramic portion.
16. The joined ceramic body according to claim 1 or 2, wherein the first ceramic portion and the second ceramic portion have a total purity of 99.99% and higher relative to a purity of 100%.
17. The joined ceramic body according to claim 1 or 2, having a purity of 99.99% and higher relative to a purity of 100%.
18. A method of manufacturing a joined ceramic body, the method comprising: a. The silicon dioxide powder is disposed between the surface of the first ceramic portion and the surface of the second ceramic portion to form a ceramic body component; b. raising the temperature of the ceramic body assembly to a sintering temperature sufficient to bond the first ceramic portion and the second ceramic portion to form the bonded ceramic body; and c. reducing the temperature of the bonded ceramic body, wherein the silica has a 25 m 2 / g to 50m 2 / g and a purity of 99.999% and higher relative to 100%, the method being characterized in that the method is carried out under conditions for preparing a joined ceramic body having the characteristics disclosed in any one of claims 1 to 17.
19. The method of claim 18, wherein step a. further comprises a powder of aluminum oxide, wherein the aluminum oxide has a purity of 99.99% and higher.
20. The method according to claim 18 or 19, wherein step a. further comprises a powder of at least one rare earth oxide having a purity of 99.99% and higher selected from the group consisting of: Y2O3, La2O3, CeO2, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Lu2O3 and combinations thereof.
21. The method according to claim 18 or 19, wherein the sintering temperature of step b. is between 1100°C and 1500°C.
22. The method according to claim 18 or 19, wherein step a. further comprises a powder of yttrium oxide having a purity of 99.995% and higher relative to 100% purity.
23. The method according to claim 18 or 19, further comprising the steps of: d. Machining the bonded ceramic body to produce a bonded ceramic body component for use in a semiconductor processing chamber.
24. The method of claim 23, wherein the bonded ceramic body component is selected from the group consisting of a dielectric window or RF window, a ring, a nozzle or gas injector, a showerhead, a gas distribution plate, an etching chamber liner, a plasma source adapter, a gas inlet adapter, a diffuser, an electronic wafer chuck, a chuck, a positioning plate, an ion suppressor element, a faceplate and / or a guard ring in an etching chamber.
25. A joined ceramic body for producing a semiconductor chamber component manufactured by a method according to any one of claims 18 to 24. 26 . The joined ceramic body according to claim 25 , having a size of 100 mm to 622 mm in each of the longest extensions with respect to the ceramic body.
27. A joined ceramic body, the joined ceramic body comprising: a. a first ceramic portion and a second ceramic portion of alumina; c. a bonding layer formed between the first ceramic part and the second ceramic part, wherein the bonding layer has a combined thickness of 0.5 μm to 20 μm, wherein the first ceramic part and the second ceramic part have a purity of 99.99% and higher, wherein the bonding layer comprises a glass ceramic, wherein the glass ceramic comprises an amorphous glass phase and at least one crystalline ceramic phase, wherein the bonding layer comprises silicon dioxide, or a combination of silicon dioxide, aluminum oxide, and at least one rare earth oxide selected from the group consisting of Y2O3, La2O3, CeO2, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Lu2O3, and wherein the bonding layer has a total purity of 99.999% and higher relative to 100% purity.
28. A joined ceramic body, the joined ceramic body comprising: a. Yttrium aluminum garnet (YAG, Y3Al5O 12 ) of a first ceramic portion and a second ceramic portion; b. a bonding layer formed between the first ceramic portion and the second ceramic portion, wherein the first ceramic portion and the second ceramic portion have a purity of 99.99% and higher, wherein the bonding layer comprises glass ceramics comprising an amorphous glass phase and at least one crystalline ceramic phase, wherein the bonding layer comprises silicon dioxide, or a combination of silicon dioxide, aluminum oxide, and at least one rare earth oxide selected from the group consisting of Y2O3, La2O3, CeO2, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Lu2O3, and wherein the bonding layer has a total purity of 99.999% and higher relative to 100% purity.
29. A plasma resistant composition, comprising: a. Silica having a particle size between 30 nm and 200 nm and a particle size between 25 nm and 200 nm as measured by the BET method. 2 / g and 50m 2 / g specific surface area; b. Alumina; and c. at least one rare earth oxide selected from the group consisting of Y2O3, La2O3, CeO2, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Lu2O3, and combinations thereof; and d. Suspending medium, Wherein the plasma resistant composition comprises a paste.
30. The plasma resistant composition of claim 29, wherein the silicon dioxide has an overall purity of at least 99.999% and higher relative to 100% purity.
31. The plasma resistant composition of claim 29 or 30, wherein the at least one rare earth oxide comprises yttrium oxide having a purity of 99.99% and greater relative to 100% purity.
32. The plasma resistant composition of claim 29 or 30, having an overall purity of at least 99.995% and higher relative to 100% purity.
33. The plasma resistant composition of claim 29 or 30, wherein the suspending medium comprises a liquid selected from the group consisting of water, ethanol, isopropanol, glycerol, and combinations thereof.
34. The plasma resistant composition of claim 29 or 30, having a maximum particle size (d100) of 4 to 6 microns.
35. The plasma resistant composition of claim 29 or 30, wherein the aluminum oxide has a purity of 99.99% and higher relative to 100% purity.
36. The plasma resistant composition of claim 29 or 30, wherein the at least one rare earth oxide selected from the group consisting of: has a purity of 99.99% and higher: Y2O3, La2O3, CeO2, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Lu2O3 and combinations thereof.
37. The plasma resistant composition of claim 29 or 30, comprising silicon dioxide in an amount of 25 to 60 weight percent, and the balance comprising a mixture of aluminum oxide in an amount of 25 to 50 weight percent and at least one rare earth oxide in an amount of 50 to 75 weight percent.
38. The plasma resistant composition of claim 37, wherein the rare earth oxide comprises yttrium oxide.
39. The plasma resistant composition of claim 38, used according to the method of any one of claims 18 to 24.
Citation Information
Patent Citations
Bonded multi-layer RF window
CN101495669A
Barium- and strontium-free vitreous or glass-ceramic jointing material and its use
CN103373813A
Solder for soldering silicon carbide ceramics in air and soldering process
CN107151147A
Ceramic bonded body and its manufacturing method
JP2010018448A